Effect of Nipple Type Drinker Height on Productive Parameters of Broilers - Quichimbo, C.; Quintana , J.; Rodriguez-Saldana, D.; Lopez-Coello, C.; Gomez, S.; Castellanos, F. (International Journal of Poultry Science, 2013)
The effect of two nipple drinker heights on productive parameters and mortality of broilers up to day 42 was assessed. Birds were subjected to two treatments: 1) low height (the bird stretches the neck and drinks on the side of the beak); and 2) at a high level (the bird stretches the neck, pushing its chest upward and drinks with the point of the beak). Height was adjusted twice per week by visual observation of the birds at drinking time and observation of bedding level homogeneity in each experimental unit. Each treatment had 5 repetitions with 7 birds each one, handling and lodging followed broiler rearing recommendations, photoperiod was natural and water temperature was maintained at the recommended range (17 and 20 °C). Variables that were recorded each week were: feed consumption, body weight, feed conversion and mortality. The data analysis showed only numeric differences for the productive parameters, although accumulated mortality was 11.4% for the lower treatment and 25.7% for the higher one (P<0.10 Also, accumulated water consumption average per treatment per bird was 10,32 L for the low treatment and 9.621 L for the high treatment. Results suggest that the height of the nipple does not affect productive parameters, nevertheless it is an important factor to guarantee the amount and quality of water that is taken in to achieve maximum yield of poultry.